The Credibility of Economic Policy Making in Argentina, 1989-2015 - Rosenblatt, David (World Bank, Washington, DC, 2016)
This paper explores the hypothesis that the credibility of economic policy making in Argentina (or lack thereof) has impacted the volatility of economic performance. To establish the link, a historical review of economic policy making and economic outcomes over the quarter century is presented, informed by a survey of the literature on credibility and the political economy of reforms. A more fundamental question is why policy shifts are so frequent, and this necessarily relates to the political institutions underlying policy making. A recent literature on citizen engagement and accountability, combined with international experience, is then used to consider policy options that could help reestablish credibility during the new administration.